A Wellness Needs Assessment of Persons with Disabilities in Northern Florida: Physical Activity and Nutrition - Stacey Griner; Jessica King; Jamie L. Pomeranz (University of North Florida, 2016)
Engaging an individual with a disability in health promotion activities may be challenging. This challenge is demonstrated by the prevalence of obesity among people with disabilities (PWDs) being higher than those without, and PWD twice as likely to be physically inactive. The combination of physical inactivity and high prevalence of obesity supports a need for health promotion activities. To examine the need for wellness promotion activities for PWDs, we surveyed consumers at a Center for Independent Living in North Central Florida (CILNCF). A survey was developed with items from the Physical Activity Scale for Individuals with Physical Disability (PASIPD) and nutrition items from Florida's Behavioral Risk Factor Surveillance System (BRFSS). Among 36 participants, 25% reported exercise was difficult due to their disability and only 6% reported their attendant assisted with exercise. Participants reported doing less than the national recommendation of medium-strength exercise (83%) and hard-strength training activities (80%). Participants reported not meeting daily guidelines for fruit (42%) and green vegetable consumption (41%). Results demonstrate a lack of physical activity and adequate nutrition among PWDs. Community service organizations such as the CILNCF represent an ideal location to administer physical activity and nutrition education and interventions.